1971
DOI: 10.1111/j.1432-1033.1971.tb01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in a Synthetic Antigen Induced by Specific Antibodies

Abstract: The high molecular weight copolymer (mol.wt. = 75000) containing the repeating sequence-(L-Tyr-L-Ala-L-G1u)-and denoted as polypeptide (Tyr-Ala-Gh), has previously been shown to possess an a-helical structure under physiological conditions. Studies were performed t o check whether monovalent fragments of antibodies derived from anti-(Tyr-Ala-Glu), antibodies could convert the partially helical oligopeptide (Tyr-Ala-Glu),, into a more helical conformation.Circular dichroic spectra of mixtures of the monovalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In two interesting studies, we could show how the combining site of the antibody can transconform the structure of the antigen. I mentioned earlier how antibodies to the ␣-helical polymer could help transconform a small polymer that was not yet helical into a helical shape (32). We could also demonstrate that the Fab of an antibody to p-azobenzenearsonate hapten may "suck out" the p-azobenzenearsonate moiety from its unavailable conformation within an ordered copolymer and convert it into another conformation, recognized by Fab (50).…”
Section: Antibodiessupporting
confidence: 52%
See 1 more Smart Citation
“…In two interesting studies, we could show how the combining site of the antibody can transconform the structure of the antigen. I mentioned earlier how antibodies to the ␣-helical polymer could help transconform a small polymer that was not yet helical into a helical shape (32). We could also demonstrate that the Fab of an antibody to p-azobenzenearsonate hapten may "suck out" the p-azobenzenearsonate moiety from its unavailable conformation within an ordered copolymer and convert it into another conformation, recognized by Fab (50).…”
Section: Antibodiessupporting
confidence: 52%
“…We distinguished between conformational (conformation-dependent) and sequential determinants (31) and showed how the same peptide (Tyr-Ala-Glu) may lead to antibodies recognizing the sequence (when attached to multichain poly-DL-alanine) or recognizing an epitope defined by conformation (when the tripeptide was polymerized to give an ␣-helical structure). In addition, we could demonstrate for the first time, by circular dichroism, how antibodies to the ␣-helical polymer could help transconform into a helical shape a small polymer that was not yet helical (32). These studies led us directly to study proteins and to synthesize a macromolecule in which a synthetic "loop" peptide derived from hen egg white lysozyme was attached to branched polyalanine (33).…”
Section: Immunogenicity and Antigenic Specificitymentioning
confidence: 99%
“…Schechter et al have shown that antibodies to the helical polypeptide (Tyr-Ala-Glu) are capable of "inducing" increased helicity in the oligopeptide (Tyr-Ala-Glu)i3 (22). Eq.…”
Section: Conformational Specificity Of Antibodiesmentioning
confidence: 99%
“…Significant reaction occurs with large peptides of the (Tyr-Ala-Glu), series (n = 4, 7, 9, 13), although circular dichroic studies indicate initial formation of helical structure only with the (Tyr-Ala-Glu),, [41]. The binding of these oligopeptides may be due to their transconformation into an a-helical form as a result of contact with the combining sites of the antibodies [42].…”
mentioning
confidence: 99%